Shake table testing of a half-scale stone masonry building aggregate - I. Tomić; A. Penna; M. DeJong; C. Butenweg; A. A. Correia; P. X. Candeias; I. Senaldi; G. Guerrini; D. Malomo; K. Beyer (Bulletin of Earthquake Engineering, 2024)
Masonry aggregates have developed throughout city centres of Europe due to a centuries-long densification process that generally lacked consistent planning or engineering. Adjacent units are connected either through interlocking stones or a layer of mortar. Without interlocking stones, the connection between the units is weak, and an out of-phase response of the units can lead to separation and pounding. Modelling guidelines and code instructions are missing for modelling the interaction of such adjacent units because of scarce experimental data. Therefore, in this study an unreinforced stone masonry aggregate was tested on the bidirectional shake table with an incremental seismic protocol as a part of the SERA AIMS—Adjacent Interacting Masonry Structures project. The aggregate was constructed at half-scale with double-leaf undressed stone masonry without interlocking between the units. Floors were built with timber beams and one layer of planks, with different beam span orientation for each unit. After significant damage, one of the units was retrofitted by anchoring the timber beams to the walls to prevent out-of-plane failure and testing was continued. Significant interaction between the units was observed with specific damage mechanisms. Cracking and separation were observed at the interface in both longitudinal and transverse direction, starting at lower intensity runs and progressively increasing. Bidirectional seismic excitation affected the unit separation, with friction forces seemingly playing a role in the transverse direction. Signs of pounding at the interface were observed during higher intensity runs, together with the formation of a soft storey mechanism at the upper storey of the higher unit. The mechanism involved an out-of-plane response of the shared wall, with a horizontal crack at the height of the interaction. These findings contribute to a better understanding of the seismic behaviour of masonry aggregates.

Shake-table testing of a stone masonry building aggregate: overview of blind prediction study - I. Tomić; A. Penna; M. DeJong; C. Butenweg; A. A. Correia; P. X. Candeias; I. Senaldi; G. Guerrini; D. Malomo; B. Wilding; D. Pettinga; M. Spanenburg; et al. (Bulletin of Earthquake Engineering, 2024)
City centres of Europe are often composed of unreinforced masonry structural aggregates, whose seismic response is challenging to predict. To advance the state of the art on the seismic response of these aggregates, the Adjacent Interacting Masonry Structures (AIMS) subproject from Horizon 2020 project Seismology and Earthquake Engineering Research Infrastructure Alliance for Europe (SERA) provides shake-table test data of a two-unit, double-leaf stone masonry aggregate subjected to two horizontal components of dynamic excitation. A blind prediction was organized with participants from academia and industry to test modelling approaches and assumptions and to learn about the extent of uncertainty in modelling for such masonry aggregates. The participants were provided with the full set of material and geometrical data, construction details and original seismic input and asked to predict prior to the test the expected seismic response in terms of damage mechanisms, base-shear forces, and roof displacements. The modelling approaches used differ significantly in the level of detail and the modelling assumptions. This paper provides an overview of the adopted modelling approaches and their subsequent predictions. It further discusses the range of assumptions made when modelling masonry walls, floors and connections, and aims at discovering how the common solutions regarding modelling masonry in general, and masonry aggregates in particular, affect the results. The results are evaluated both in terms of damage mechanisms, base shear forces, displacements and interface openings in both directions, and then compared with the experimental results. The modelling approaches featuring Discrete Element Method (DEM) led to the best predictions in terms of displacements, while a submission using rigid block limit analysis led to the best prediction in terms of damage mechanisms. Large coefficients of variation of predicted displacements and general underestimation of displacements in comparison with experimental results, except for DEM models, highlight the need for further consensus building on suitable modelling assumptions for such masonry aggregates.